2004
DOI: 10.1084/jem.20040773
|View full text |Cite
|
Sign up to set email alerts
|

The Same IκBα Mutation in Two Related Individuals Leads to Completely Different Clinical Syndromes

Abstract: Both innate and adaptive immune responses are dependent on activation of nuclear factor κB (NF-κB), induced upon binding of pathogen-associated molecular patterns to Toll-like receptors (TLRs). In murine models, defects in NF-κB pathway are often lethal and viable knockout mice have severe immune defects. Similarly, defects in the human NF-κB pathway described to date lead to severe clinical disease. Here, we describe a patient with a hyper immunoglobulin M–like immunodeficiency syndrome and ectodermal dysplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(99 citation statements)
references
References 27 publications
3
95
0
1
Order By: Relevance
“…These results suggest that the NF-kB signal transduction pathway is disturbed in both cell types. The degree of GH insensitivity in the present patient is similar to that reported by Wu et al, but the immune problems in the patient with the IkBa mutation were far more severe (16,31). Our patient had a mild hypogammaglobulinemia and recurrent infections responding to antibiotics, suggesting that the observed impairment of immunity is mainly limited to the humoral immune response.…”
Section: Discussionsupporting
confidence: 75%
“…These results suggest that the NF-kB signal transduction pathway is disturbed in both cell types. The degree of GH insensitivity in the present patient is similar to that reported by Wu et al, but the immune problems in the patient with the IkBa mutation were far more severe (16,31). Our patient had a mild hypogammaglobulinemia and recurrent infections responding to antibiotics, suggesting that the observed impairment of immunity is mainly limited to the humoral immune response.…”
Section: Discussionsupporting
confidence: 75%
“…In our case, these mechanisms enable Nkx3.2 to cause persistent NF-B activation, which, in turn, supports chondrocyte survival. In addition, we interestingly observed that functionally intact IKK␤ and NEMO are required for viability maintenance in multiple (16,17,28,43). While these previous studies did not address molecular mechanisms responsible for constitutive IKK and/or NF-B activation in chondrocytes, our current study may provide a molecular explanation as to how a nuclear factor such as Nkx3.2 can enable steady-state IKK activation leading to constitutive NF-B activation, which can be associated with cell viability maintenance in chondrocytes (28,43).…”
Section: Discussionmentioning
confidence: 94%
“…61,62 This new autosomal dominant form of EDA-ID shares many similarities with NEMO-related EDA-ID, but is also characterized by an unusual feature. It is associated with severely impaired T cell proliferation, something that is not observed with NEMO mutated patients.…”
Section: Eda-id (Autosomal Dominant Form)mentioning
confidence: 99%